Impact of Echinococcus granulosus Cyst Fluid on the Phenotypic Dynamics and Degranulation of RBL-2H3 Mast Cells - Yue Z; Zhou JR; Wang CS; Pu XL; Parehati G; Cao LW; Bayina B; Ye JR (Journal of Inflammation Research)
Zhen Yue,1,2,* Jing-Ru Zhou,3,* Chun-Sheng Wang,1 Xue-Li Pu,1 Guligeiya Parehati,1 Li-Wei Cao,1 Batesurong Bayina,1 Jian-Rong Ye1 1Department of Anesthesiology, The First Affiliated Hospital of Xinjiang Medical University, Urumqi, 830054, People’s Republic of China; 2Department of Anesthesiology, Changji People’s Hospital, Changji, 831100, People’s Republic of China; 3Department of Anesthesiology, The Sixth Affiliated Hospital of Xinjiang Medical University, Urumqi, 830063, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jian-Rong Ye, Department of Anesthesiology, The First Affiliated Hospital of Xinjiang Medical University, No. 137, Liyushan South Road, Urumqi, 830054, People’s Republic of China, Tel +86 18999938777, Email ywjianrongym@126.comObjective: This study aimed to evaluate the effects of Echinococcus granulosus cyst fluid (EgCF) on the phenotypic characteristics and degranulation activity of mast cells during echinococcosis-associated hypersensitivity reactions, using the RBL-2H3 rat basophilic leukemia cell line as an in vitro model.Methods: The cytotoxic effects of EgCF on RBL-2H3 cells were assessed using the Cell Counting Kit-8 assay. Degranulation activity was quantified by measuring β-hexosaminidase release. Morphological alterations and cytoskeletal changes were evaluated via toluidine blue staining and phalloidin-labeled confocal laser scanning microscopy. Apoptotic cell populations were quantified using flow cytometry.Results: EgCF at mass concentrations ranging from 0.5 to 5 mg/mL significantly enhanced cell proliferation. Higher EgCF concentrations were associated with increased morphological deformation, as evidenced by toluidine blue staining, and with significantly elevated β-hexosaminidase release compared to the control group (p < 0.01). Flow cytometry revealed a statistically significant increase in apoptosis rates in the treated groups (p < 0.01). Within 30 minutes of EgCF exposure, phalloidin staining showed notable cytoskeletal reorganization, including cellular wrinkling and pseudopodia extension. These morphological changes were partially reversed within 45 to 60 minutes.Conclusion: EgCF induces morphological transformation and promotes degranulation in mast cells, with the intensity of these responses correlating positively with EgCF concentration. These findings suggest a dose-dependent role of EgCF in modulating mast cell activity during parasitic hypersensitivity responses.Keywords: allergic hypersensitivity, Echinococcus granulosus cyst fluid, mast cell degranulation, parasitic infection, RBL-2H3 cells